Perbandingan penggunaan model pembelajaran berbasis projek dan berbasis masalah dalam proses belajar Matematika (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Project Based learning and Problem based learning in Math had differences usage, this study will finding the differences usage between them , and also to look for a best model to determining of a variable. This research was conducted at covid 19 pandemic. So, literature study is my way to get  data. Obtained 11 researches from various sources through the Google search engine. there were 2 studies that produced research that had no effect on the variables Of the 11 studies. Thus the PBL model was accepted to be superior at 61.53% and the PjBLl at 38.46%. The result of this study described that Problem Based Learning is very well used to improve student learning outcomes, student critical thinking, and student learning styles. Whereas the Project Based Learning is very well used to improve students creative abilities, students communication skills and things related to something concrete.
Keywords: Project Based Learning; Problem Based Learning